The asymmetrical bank-client relationship Case of Algerian public banks - SENOUCI, Kouider; MERAD, Mohammed Djamil (International Journal of Scientific Research and Management (IJSRM), 2021)
Asymmetric information remains one of the most crucial problems in finance, though many  works  have  been  produced  since  the  first  writings  of  Akerloff,  Spence  and  Stiglitz and many others. The inequality of getting information causes many problems to entreprises, because  the  responsible  needs  all  information  to  solve  these problems  and  decides  what solution  should  fulfil the purpose in vew.  In  this  context,  the information and communication technologies (ICT)  play  a  dominant  role  for  the  spreading  of information to different users and researchers. The present work is articulated around two main parts.  The first deals with the theoretical aspects of asymmetric information.  The second is an empirical approach realised using a sample of questions in Algerian public Banks. All the questions deal with the impact of asymmetric information on the banking activity.